Sodium-ion battery negative electrode material with monatomic sodium-philic sites as well as preparation and application of sodium-ion battery negative electrode material

By introducing single-atomic sodium-philic sites into hard carbon materials, the problems of slow sodium ions migration rate and low reversible capacity in hard carbon negative electrode materials are solved, and the energy density of sodium ion batteries is significantly improved.

CN119660714AActive Publication Date: 2025-03-21SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411989234.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The slower sodium ion migration rate and lower reversible capacity in existing hard carbon anode materials limit the energy density of sodium ion batteries.

Method used

Sodium lignin sulfonate and metal salt were used for hydrothermal reaction, and then mixed with a nitrogen source for high temperature carbonization to prepare a sodium ion battery negative electrode material with a single atomic sodium-philic site.

Benefits of technology

By introducing single-atom sodium-philic sites, the migration rate of sodium ions is significantly improved, and the rate performance and reversible capacity of hard carbon materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660714A_ABST
    Figure CN119660714A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion batteries, and particularly relates to a sodium-ion battery negative electrode material with monatomic sodium-philic sites as well as preparation and application of the sodium-ion battery negative electrode material. The method comprises the following steps: (I) dissolving sodium lignin sulfonate and metal salt in water according to a ratio, and putting the solution into a high-temperature and high-pressure reaction kettle for hydrothermal reaction; and (II) filtering, cleaning and drying a product after the hydrothermal reaction, mixing the product with a nitrogen source, and performing high-temperature carbonization in a high-temperature tubular furnace to obtain the sodium ion battery negative electrode material. In the preparation method, the hydrothermal product added with the metal salt is directly carbonized at a high temperature to prepare the hard carbon negative electrode material with rich micropore content, and the sodium ion battery negative electrode material with a monatomic sodium-philic site can be prepared by further converging a nitrogen source and carbonizing at a high temperature in the step II. According to the invention, the problems of slow sodium ion migration rate and relatively low reversible capacity in the existing hard carbon negative electrode material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery negative electrode material having a single-atom sodium-philic site, and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have become a new generation of large-scale grid energy storage systems that promote the global carbon neutrality process due to their abundant sodium reserves, low production costs and safety. As the research on positive electrode materials (layered oxides, Prussian blue, etc.) becomes more and more mature and meets the requirements of commercial production applications, how to develop suitable negative electrode materials has become a prerequisite for the large-scale commercialization of sodium-ion batteries.

[0003] As a non-graphitizable carbon, hard carbon has become the most suitable negative electrode material for sodium-ion batteries due to its graphite microcrystalline region suitable for sodium ion embedding (interlayer spacing greater than 0.37nm) and rich hierarchical pore structure. However, since the sodium storage mechanism of hard carbon is still controversial at this stage (the typical charge and discharge curve of hard carbon includes sodium storage in the slope area above 0.1V and sodium storage in the platform area below 0.1V), the capacity in the low-voltage area and the slow sodium ion migration rate have become important factors restricting the energy density of sodium-ion batteries. Summary of the invention

[0004] In order to solve the problems of slow sodium ion migration rate and low reversible capacity in existing hard carbon negative electrode materials, the primary purpose of the present invention is to provide a sodium ion battery negative electrode material with a single-atom sodium-philic site.

[0005] Another object of the present invention is to provide a method for preparing a negative electrode material for a sodium ion battery having a single-atom sodium-philic site.

[0006] Another object of the present invention is to provide an application of the above-mentioned sodium ion battery negative electrode material having a single-atom sodium-philic site.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a sodium ion battery negative electrode material having a single-atom sodium-philic site comprises the following steps:

[0009] (I) dissolving sodium lignin sulfonate and a metal salt in water in proportion and performing a hydrothermal reaction;

[0010] (II) filtering, washing, and drying the product after the hydrothermal reaction, mixing it with a nitrogen source, and subjecting it to high-temperature carbonization to obtain the negative electrode material for a sodium ion battery.

[0011] Furthermore, in step I, the sodium lignin sulfonate is a by-product extracted from papermaking black liquor.

[0012] Furthermore, in step I, the metal salt is one or more transition metal salts such as zinc chloride, ferric chloride, cobalt chloride, nickel chloride, cupric chloride, manganese chloride, magnesium chloride, etc., and zinc chloride is most preferred.

[0013] Furthermore, in step I, the mass ratio of the sodium lignin sulfonate to the metal salt is 1:0.1 to 1:5.

[0014] Furthermore, in step I, the solvent of the hydrothermal reaction is one or more of water and ethanol, and preferably the solvent is water.

[0015] Furthermore, in step I, the solid-liquid ratio in the hydrothermal reaction is 1:2 to 1:10 (g / mL), preferably 1:10 (g / mL).

[0016] Furthermore, in step I, the temperature of the hydrothermal reaction is 100-250°C, the time of the hydrothermal reaction is 2-12h, and the heating rate of the hydrothermal reaction is 10°C / min; preferably, the temperature of the hydrothermal reaction is 200-250°C, and the reaction time is 4-12h; most preferably, the temperature of the hydrothermal reaction is 200°C, and the reaction time is 4h.

[0017] Furthermore, in step II, the nitrogen source is one or more nitrogen-containing salts such as ammonium chloride, urea, ammonium oxalate, ammonium sulfate, ammonium nitrate, etc., preferably ammonium chloride.

[0018] Furthermore, in step II, the mass ratio of the hydrothermal reaction product to the nitrogen source is 1:0.5 to 1:10, the mass ratio of the hydrothermal reaction product to the nitrogen source is 1:3 to 1:8, and most preferably is 1:5.

[0019] Furthermore, in step II, the mixing method is ball milling, that is, the solid powder is crushed and mixed uniformly;

[0020] Furthermore, in step II, the high-temperature carbonization program is divided into two stages, first heating to 600-900°C and keeping warm for 1-4 hours, then continuing to heat to 1000-1400°C and keeping warm for 1-4 hours, the carbonization heating rate is 5°C / min, and the carbonization atmosphere is one or more of nitrogen and argon; more preferably, the insulation temperature of the first stage is 800-900°C, and the insulation temperature of the second stage is 1300-1400°C; most preferably, the insulation temperature of the first stage is 800°C, and the insulation temperature of the second stage is 1300°C.

[0021] Furthermore, in step II, the carbonized product needs to be cleaned, ground and dried, and finally a sodium ion battery negative electrode material with a single-atom sodium-philic site is obtained.

[0022] Furthermore, the present invention also discloses a sodium ion battery negative electrode material having a single-atom sodium-philic site, which is prepared by the preparation method.

[0023] Furthermore, the present invention also discloses a sodium ion battery assembled from the above-mentioned sodium ion battery negative electrode material.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] The present invention selects lignin sulfonate from papermaking black liquor waste as raw material to prepare hard carbon negative electrode products with high added value, thereby reducing environmental pollution and realizing the value-added utilization of papermaking black liquor waste.

[0026] In the preparation method of the present invention, the hydrothermal product after adding the metal salt is directly carbonized at high temperature to prepare a hard carbon negative electrode material with rich micropore content, and in step II, a nitrogen source is further combined with high temperature carbonization to prepare a sodium ion battery negative electrode material with a single atom sodium-philic site. The method of the present invention is highly flexible and has excellent performance in preparing hard carbon.

[0027] In the preparation method of the present invention, when the metal salt is zinc chloride, the sodium ion battery negative electrode material with single-atom sodium-philic sites greatly improves the sodium ion migration rate by introducing metal single-atom sites (ZnN4C) inside the hard carbon material, thereby improving the rate performance of the hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly explain the technical solutions adopted by the embodiments of the present invention or the prior art, the drawings involved in the embodiments or the prior art description are briefly introduced below. It should be noted that these drawings only represent some embodiments of the present invention, and those skilled in the art can derive other related drawings based on these drawings without creative efforts.

[0029] Figure 1 The sodium ion battery charge and discharge curves of the sodium ion battery negative electrode materials prepared in Example 1, Comparative Example 7 and Comparative Example 9 of the present invention, the experimental results are all stable data repeated three times;

[0030] Figure 2 The sodium ion battery rate performance diagram of the sodium ion battery negative electrode materials prepared in Example 1, Comparative Example 7 and Comparative Example 9 of the present invention, the experimental results are all stable data repeated three times;

[0031] Figure 3 The cycle stability diagram of the sodium ion battery negative electrode material prepared in Example 1 of the present invention and Comparative Example 9 at a current density of 3A / g, and the experimental results are all stable data repeated three times;

[0032] Figure 4The pore structure distribution diagram of the sodium ion battery negative electrode material prepared in Example 1, Comparative Example 7 and Comparative Example 9 of the present invention;

[0033] Figure 5 This is a spherical aberration electron microscope image of the sodium ion battery negative electrode material prepared in Example 1 of the present invention;

[0034] Figure 6 The rate performance diagram of the sodium ion battery negative electrode material prepared in Examples 2-7 of the present invention, the experimental results are all stable data repeated three times;

[0035] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] In order to clearly show the objectives, technical solutions and advantages of the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be fully and accurately described below. It should be clear that the following examples are only used to illustrate the present invention, rather than to limit it. Unless otherwise explicitly stated, all technical terms and scientific terms used herein follow the common definitions in the technical field, and the reagents mentioned all reach industrial or analytical purity standards. In addition, the drawings and descriptions provided are intended to help those skilled in the art to have a deeper understanding of the present application, rather than to limit the subject matter covered by the claims.

[0037] As used herein, "ranges" are defined by setting lower limits and upper limits, which define the boundaries of a particular range. Such ranges may or may not include their end values ​​and may be freely combined, i.e., any lower limit may be combined with any upper limit to form a new range.

[0038] Unless otherwise specified, all embodiments and optional solutions in this application can be combined with each other to create new technical solutions. Similarly, unless otherwise specified, all technical features and optional features in this application can also be combined with each other to form new technical solutions.

[0039] The present invention is described in detail below, which comprises the following specific steps:

[0040] (I) dissolving sodium lignin sulfonate and metal salt extracted from papermaking black liquor in water in a certain proportion and placing the mixture in a high-temperature and high-pressure reactor for hydrothermal reaction;

[0041] (II) filtering, washing and drying the product after the hydrothermal reaction, mixing it with a nitrogen source, and placing it in a high-temperature tube furnace for high-temperature carbonization to obtain the sodium ion battery negative electrode material having a single-atom sodium-philic site.

[0042] Example 1

[0043] (I) dissolving sodium lignin sulfonate and zinc chloride extracted from papermaking black liquor in 200 mL of water at a mass ratio of 1:5 and placing the mixture in a high-temperature and high-pressure reactor for hydrothermal reaction at 200° C. for 4 h;

[0044] (II) The product after the hydrothermal reaction is filtered, washed with water and dried, and then mixed with ammonium chloride (the mass ratio of the hydrothermal reaction product to ammonium chloride is 1:5), and placed in a high-temperature tube furnace and heated to 800°C for 2 hours, and then continued to heat to 1300°C for 3 hours. The cooled material is then washed in 1 mol / L hydrochloric acid solution and water for 6 hours, and dried to obtain the sodium ion battery negative electrode material having a single atom sodium-philic site.

[0045] Example 2

[0046] Example 2 refers to the preparation process of Example 1, except that the metal salt in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is ferric chloride.

[0047] Example 3

[0048] Example 3 refers to the preparation process of Example 1, except that the metal salt in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is cobalt chloride.

[0049] Example 4

[0050] Example 4 refers to the preparation process of Example 1, except that the metal salt in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is nickel chloride.

[0051] Example 5

[0052] Example 5 refers to the preparation process of Example 1, except that the metal salt in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is copper chloride.

[0053] Example 6

[0054] Example 6 refers to the preparation process of Example 1, except that the metal salt in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is manganese chloride.

[0055] Example 7

[0056] Example 7 refers to the preparation process of Example 1, except that the metal salt in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is magnesium chloride.

[0057] Example 8

[0058] Example 8 refers to the preparation process of Example 1, except that the nitrogen salt in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is ammonium sulfate.

[0059] Example 9

[0060] Example 9 refers to the preparation process of Example 1, except that the nitrogen salt in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is urea.

[0061] Example 10

[0062] Example 10 refers to the preparation process of Example 1, except that the nitrogen salt in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is ammonium nitrate.

[0063] Embodiment 11

[0064] Example 11 refers to the preparation process of Example 1, except that the nitrogen salt in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is ammonium oxalate.

[0065] Comparative Example 1

[0066] Comparative Example 1 refers to the preparation process of Example 1, except that the hydrothermal reaction temperature in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is 100 degrees Celsius.

[0067] Comparative Example 2

[0068] Comparative Example 2 refers to the preparation process of Example 1, except that the hydrothermal reaction time in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site is 2 h.

[0069] Comparative Example 3

[0070] Comparative Example 3 refers to the preparation process of Example 1, except that: in step I of preparing the sodium ion battery negative electrode material with a single-atom sodium-philic site, the mass ratio of sodium lignin sulfonate to metal salt is 1:10.

[0071] Comparative Example 4

[0072] Comparative Example 4 refers to the preparation process of Example 1, except that ammonium chloride is added in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site, and the mass ratio of the hydrothermal reaction product to ammonium chloride is 1:2.

[0073] Comparative Example 5

[0074] Comparative Example 5 refers to the preparation process of Example 1, except that ammonium chloride is added in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site, and the mass ratio of the hydrothermal reaction product to ammonium chloride is 1:10.

[0075] Comparative Example 6

[0076] Comparative Example 6 refers to the preparation process of Example 1, except that: in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site, the first carbonization temperature is 600°C.

[0077] Comparative Example 7

[0078] Comparative Example 7 refers to the preparation process of Example 1, except that no metal salt is added in step I of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site.

[0079] Comparative Example 8

[0080] Comparative Example 8 refers to the preparation process of Example 1, except that: in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site, the second carbonization temperature is 1200°C.

[0081] Comparative Example 9

[0082] Comparative Example 9 refers to the preparation process of Example 1, except that no nitrogen salt is added in step II of preparing the sodium ion battery negative electrode material with a single atom sodium-philic site.

[0083] The sodium ion battery negative electrode materials having single-atom sodium-philic sites prepared in the embodiments of the present invention and the comparative examples were analyzed and tested, as follows:

[0084] Electrochemical performance test: The electrochemical performance of sodium-ion battery negative electrode materials with single-atom sodium-philic sites is usually tested in a half-cell system using a Xinwei button cell system, using 1 mol / L NaPF6 as the electrolyte.

[0085] The constant current charge-discharge method (GCD) test was carried out on the Xinwei button battery test system. The test procedure was to discharge first and then charge. The charge and discharge test currents were 0.02A / g, 0.05A / g, 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 3A / g, and 0.02A / g, respectively, and 5 cycles were performed at each current density to obtain the first cycle charge and discharge curve and rate performance curve of the prepared material. The corresponding cycle stability test was performed by setting the current density to 3A / g and cycling 5000 cycles.

[0086] Specific surface area and pore structure (BET) analysis, using micropore analyzer (ASAP2060) at 77K (liquid nitrogen bath) and 273K (ice water bath) conditions for dry nitrogen and carbon dioxide isothermal adsorption analysis of the sample. Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) analysis theory equivalent to calculate the sample surface area, pore sample diameter and pore volume.

[0087] Depend on Figure 1 From the first charge and discharge curves, we can see that after the introduction of metal salt for hydrothermal reaction, the comparative example 9 prepared by direct carbonization has an initial coulombic efficiency of 84.5% and a first-cycle charge capacity of 302 mAh / g. After further carbonization by introducing a nitrogen source, the prepared embodiment 1 with ZnN4C sodium-philic sites has an initial coulombic efficiency of 88.7% and a first-cycle charge capacity of 342 mAh / g, which are significantly improved compared with the initial coulombic efficiency of 59.8% and the first-cycle charge capacity of 160 mAh / g of the blank comparative example 7.

[0088] Depend on Figure 2 From the rate performance curve, it can be seen that the comparative example 9 prepared by introducing metal salt hydrothermal carbonization pore formation and the example 1 introducing single-atom sodium-philic sites have better rate performance than the blank comparative example 7 sample, which further verifies the feasibility of metal salt-assisted hydrothermal carbonization and single-atom sites to improve the sodium ion migration efficiency.

[0089] Depend on Figure 3 It can be seen from the cyclic stability curve that after further introducing the single-atom sodium-philic site ZnN4C, in addition to the improved reversible capacity and rate performance of the material, the ZnN4C site can further promote the uniform formation of the SEI film on the surface of the hard carbon negative electrode, thereby improving its stability. Therefore, compared with Example 9, Example 1 shows better stability after 5000 cycles at a large current of 3A / g, further proving the important role of the single-atom sodium-philic site of ZnN4C.

[0090] Depend on Figure 4 From the pore size distribution diagram, it can be seen that the introduction of metal salts during the hydrothermal process (Comparative Example 9) can significantly increase the micropore and mesopore content in the hard carbon material, which is beneficial to further sodium storage. After the further introduction of nitrogen source (Example 1), due to the anchoring effect of the nitrogen source, the volatilization of zinc is hindered, and the mesopore content is further reduced compared with Comparative Example 7, and is replaced by a microporous structure that is more conducive to sodium storage.

[0091] Figure 5This is a spherical aberration electron microscopy image of the sodium ion battery negative electrode material prepared in Example 1, in which the distributed bright dots are the ZnN4C single-atom sodium-philic sites introduced into the hard carbon material.

[0092] Figure 6 This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Example 2-7. It can be seen from the figure that, thanks to the lower volatilization temperature of zinc, its performance is excellent among all metal salts of the same type.

[0093] In order to better reflect the differences between the embodiments and comparative examples, the test results of the embodiments and comparative examples are summarized in Table 1.

[0094] Table 1 Test results of Examples 1-11 and Comparative Examples 1-9

[0095]

[0096] From the analysis in the table, it can be seen that due to the difference in the volatilization temperature of different metal oxides formed after different metal salts are heated in the subsequent carbonization process, the performance differences between different metal salts (Example 2-Example 7) are relatively large. This is because particles such as iron oxide and manganese oxide are difficult to volatilize at high temperatures and remain inside the carbon material, which will induce the formation of transitional graphitization, resulting in the hard carbon material prepared not having an interlayer spacing suitable for sodium embedding. At the same time, for different nitrogen sources, there are also significant differences in their anchoring effect on metallic zinc. Example 8 uses ammonium sulfate as a nitrogen source to anchor zinc atoms. Although it has a reversible capacity of 341 mAh / g, due to the introduction of additional sulfur elements in the process, additional defect sites will be introduced, resulting in a significant reduction in the first-cycle coulomb efficiency, while nitrogen sources such as ammonium nitrate, urea, and ammonium oxalate are relatively poor.

[0097] The data of Comparative Examples 1 to 9 further explain that the construction of this single-atom sodium-philic site is affected by the nitrogen source ratio and carbonization temperature. A high nitrogen source ratio will lead to an increase in defect content and a decrease in the first effect, while a low ratio will lead to a decrease in the number of sites and poor performance.

[0098] The above experimental results prove that the metal salt hydrothermal method used in the present invention can greatly improve the first cycle coulombic efficiency and reversible capacity of hard carbon materials by adding a nitrogen source during the carbonization process and introducing single-atom sodium-philic sites, while inducing the formation of a uniform SEI film and improving its cycle stability. The present invention not only achieves the reduction and efficiency improvement of papermaking black liquor waste from the raw material, but also has simple operation in the process, and can prepare sodium ion battery negative electrode materials with excellent performance and single-atom sodium-philic sites.

[0099] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a sodium ion battery negative electrode material having a single-atom sodium-philic site, characterized in that: It includes the following steps: (I) dissolving sodium lignin sulfonate and a metal salt in water in proportion and performing a hydrothermal reaction; (II) filtering, washing and drying the product after the hydrothermal reaction, mixing it with a nitrogen source, and subjecting it to high-temperature carbonization to obtain the negative electrode material for a sodium ion battery.

2. The preparation method according to claim 1, characterized in that: In step I, the metal salt is one or more of zinc chloride, ferric chloride, cobalt chloride, nickel chloride, copper chloride, manganese chloride and magnesium chloride.

3. The preparation method according to claim 1, characterized in that: In step I, the mass ratio of the sodium lignin sulfonate to the metal salt is 1:0.1 to 1:

5.

4. The preparation method according to claim 1, characterized in that: In step I, the solvent of the hydrothermal reaction is one or more of water and ethanol; The solid-to-liquid ratio in the hydrothermal reaction is 1:2 to 1:10 g / mL.

5. The preparation method according to claim 1, characterized in that: In step I, the temperature of the hydrothermal reaction is 100-250° C., and the time of the hydrothermal reaction is 2-12 h.

6. The preparation method according to claim 1, characterized in that: In step II, the nitrogen source is one or more of ammonium chloride, urea, ammonium oxalate, ammonium sulfate, and ammonium nitrate.

7. The preparation method according to claim 1, characterized in that: In step II, the mass ratio of the hydrothermal reaction product to the nitrogen source is 1:0.5 to 1:

10.

8. The preparation method according to claim 1, characterized in that: In step II, the high temperature carbonization procedure is divided into two stages, firstly heating to 600-900°C and keeping warm for 1-4h, then continuing to heat to 1000-1400°C and keeping warm for 1-4h, the carbonization heating rate is 5°C / min, and the carbonization atmosphere is one or more of nitrogen and argon.

9. A sodium ion battery negative electrode material having a single-atom sodium-philic site, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: The negative electrode is the negative electrode material for a sodium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • ACTIVE CHARCOAL MANUFACTURING PROCESS

    BE823423A

  • Cobalt-nickel sulfide / nitrogen-doped carbon nano-fiber composite material, preparation method and application thereof

    CN106298269A

  • C / C70 / CaS composite negative electrode material for sodium-ion battery and preparation method of C / C70 / CaS composite negative electrode material

    CN107681137A

  • High-first-effect hard carbon negative electrode for sodium ion battery

    CN115417398A

  • High-mesoporous-rate nitrogen and sulfur double-doped lignin-based carbon material as well as preparation and application thereof

    CN116199206A

Cited By

  • Hard carbon paper negative electrode material based on TEMPO oxidation modification and preparation method and application thereof

    CN121757839A